2018
DOI: 10.1111/liv.13668
|View full text |Cite
|
Sign up to set email alerts
|

Is global elimination of HCV realistic?

Abstract: The elimination of hepatitis C virus (HCV) has been made possible through the availability of new antiviral drugs which may now be administered to all patients with HCV infection, even those with decompensated cirrhosis. The goal of the World Health Organization (WHO) is to reduce the incidence of chronic hepatitis infection from the current 6-10 million to 0.9 million cases of chronic infections by 2030, and annual deaths from 1.4 million to fewer than 0.5 million. Achieving these targets will require

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…HBV vaccination programmes have been widely implemented in countries around the globe, and eradication of HCV through the use of direct-acting antivirals is a target in many others. 61,62 While virally induced tumours will soon become less frequent, alcoholrelated cirrhosis is a stably prevalent pre-neoplastic condition, and chronic fatty liver disease associated with metabolic syndrome is a growing cause of HCC even in the absence of cirrhosis. 63 All these changes will have an impact on surveillance policies that Singal et al review nicely in this special issue.…”
Section: Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“…HBV vaccination programmes have been widely implemented in countries around the globe, and eradication of HCV through the use of direct-acting antivirals is a target in many others. 61,62 While virally induced tumours will soon become less frequent, alcoholrelated cirrhosis is a stably prevalent pre-neoplastic condition, and chronic fatty liver disease associated with metabolic syndrome is a growing cause of HCC even in the absence of cirrhosis. 63 All these changes will have an impact on surveillance policies that Singal et al review nicely in this special issue.…”
Section: Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 99%
“…However, direct-acting antiviral drugs (DAAs) represent a vast improvement on earlier treatment regimens and offer cure rates upwards of 100% [24]. The current barriers to treatment for HCV with DAAs are primarily around cost and access [25], especially among people who use drugs [26]. …”
Section: Epidemiology Of Rural Opioid Epidemicmentioning
confidence: 99%
“…Moreover, a recent review by Calcvaruso et al evaluated whether global elimination of HCV is a realistic goal . They concluded that the differences in the prevalence of HCV throughout the world, as well as in populations, ages, risk factors and disparities in the costs of drugs and the availability of funds will make reaching this goal difficult.…”
Section: Introductionmentioning
confidence: 99%